Utilization of aluminum dross as a cement replacement material for sustainable concrete development - Mohd Zahari, Nur Hidayah; Salmiaton, Ali; Sobri, Shafreeza; Mohd Nasir, Noor Azline; Ishak, Nor Shafizah (Universiti Putra Malaysia Press, 2024)
The recovery of aluminum from aluminum dross waste involves intensive cost and energy. Therefore, there is a need for its utilization as an engineering material by using it as a filler material in concrete production. The cement industry is battling numerous difficulties due to the shortage of raw materials and sustainability issues related to the emission of CO2 into the atmosphere. On this basis, the present study aims to utilize aluminum dross as a replacement material for cement to develop sustainable concrete. In this study, the results of control concrete samples were compared to the results of concrete samples containing aluminum dross by 5%, 10%, and 15% by weight of cement. The mechanical and chemical analysis of the M40 grade concrete employing aluminum dross as a replacement material in cement was analyzed. It was noticed that the best percentage of aluminum dross was 10%, providing better results compared with conventional concrete. It recorded the highest strength of 41.3MPa. Thermogravimetric analysis was conducted in which weight loss, decomposition of hydration compounds, and percentage of calcium hydroxide from concrete were determined. Scanning electron microscopy analysis showed that the density of concrete increased owing to the presence of ettringite needles and calcium silicate hydrate in the matrix. Moreover, the toxicity analysis revealed that the ammonia content and the leachability of trace elements from the concrete were both low and within acceptable ranges. The findings indicate that aluminum dross has positive results as an additional cementitious material in concrete to overcome environmental problems related to dross management and reduce cement utilization, producing more sustainable concrete. © Universiti Putra Malaysia Press.